Identificação dos princípios tóxicos de Cestrum Axillare (Cestrum Laevigatum) - Jéssica Baeca Rezende Marinho (2017)
Cestrum axillare (formerly C. laevigatum) family Solanaceae, is the most important hepatotoxic plant in Brazil that causes acute poisoning. It occurs in the Southeast and Center-West regions and in coastal areas of the Northeast Brazil. Spontaneous poisoning was described in cattle, goats and sheep, with clinical signs evidenced within 24 hours after ingestion of the leaves and death within 48 hours after signs onset. The clinical signs observed in acute poisoning are apathy, anorexia, ruminal arrest, arched back, constipation with feces in small spheres, sometimes covered with mucus and blood streaks, muscle tremors, staggering gait and sometimes sialorrhoea. Neurological signs may be observed, due to interference in the urea cycle due to hepatic insufficiency resulting in hyperammonemia (hepatic encephalopathy). The main pathological finding is centrilobular hepatic necrosis. The toxic principle present in C. axillare was not yet definitively proven, but some authors attribute the toxicity of the plant to the presence of saponins gitogenin and digitogenin. However, C. axillarepoisoning is characterized by centrilobular hepatic necrosis, similar to those observed in plants poisoning containing carboxyatractyloside compounds, such as Atractylis grummifera, Cestrum parqui and Xantium spp. Therefore, it is necessary to determine if the toxic effects resulting from the ingestion of the C. axillare leaves are produced by saponins or carboxyatractylosides. Thus, the objective of this work was to determine which are the compounds responsible for the toxic effects produced by the ingestion of the leaves of C.axillare. For this, the effects of the administration of the leaves were compared with those produced by the saponins isolated from the leaves in goats. Subsequently, it was determined by chromotography whether the leaves of C. axillare contain carboxyatractylosides. Six goats were randomly assigned to three experimental groups that received [1] dry leaves of C. axillare, [2] saponins extract from leaves or [3] water (control group). For goats receiving the dry leaves the administered dose of plant was 10 g/kg for one animal (A1) and 5 g/kg for the other one (A2). For animals receiving the saponins extract, administration was done at a dose equivalent to 20 g/kg repeated after 24 hours. The dry leaves administered at a dose of 10 g/kg to a goat produced toxic effects, with alterations in biochemistry (indicating hepatic lesion) and histopathology showing centrilobular hepatic necrosis. At the dose of 5 g/kg of dry leaves, clinical signs of poisoning were not observed, but hepatic necrosis was found; after 15 days after the last administration, the hepatic parenchyma of this animal was already normal, with only hemorrhagic areas, demonstrating full regeneration. The administration of extracts of saponins containing gitogenin and digitogenin to goats did not produce significant toxic effects, proving that these compounds are not responsible for intoxication. The phytochemical study of the leaves of the plant demonstrated the presence of carboxyatractylosides, compounds that are responsible for the same toxic effects observed in C. axillare poisoning. Thus, the toxic principle responsible for cases of C. axillare poisoning is carboxyatractyloside. In addition, goats are a good experimental model for studies of this intoxication.